2017
DOI: 10.1002/path.4988
|View full text |Cite
|
Sign up to set email alerts
|

Chronic psychological stress promotes lung metastatic colonization of circulating breast cancer cells by decorating a pre‐metastatic niche through activating β‐adrenergic signaling

Abstract: Numerous studies have indicated that primary tumors induce the formation of a pre-metastatic niche in distant organs by secreting tumor-derived factors. The present study shows that pre-exposure to chronic stress enhanced lung colonization efficiency by circulating tumor cells, suggesting that chronic stress critically influences pre-metastatic lungs before the arrival of disseminated tumor cells. Ablation of the sympathetic nerve function by 6-OHDA or blockage of the -adrenergic signaling by propranolol rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 42 publications
1
82
1
4
Order By: Relevance
“…Epidemiologic studies have long reported that psychological and social conditions, such as low social support, can affect the progression of some cancers (65), including the development of metastasis (66). There is also some evidence that molecular profiles of tumors may be affected by psychosocial conditions (67,68), and the emerging fields of psycho-oncology and social genomics have been nicely reviewed (69).…”
Section: A Higher Regulation Level Of Cancer Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiologic studies have long reported that psychological and social conditions, such as low social support, can affect the progression of some cancers (65), including the development of metastasis (66). There is also some evidence that molecular profiles of tumors may be affected by psychosocial conditions (67,68), and the emerging fields of psycho-oncology and social genomics have been nicely reviewed (69).…”
Section: A Higher Regulation Level Of Cancer Developmentmentioning
confidence: 99%
“…Various studies have shown that nerve density is increased in primary human tumors and that there is an association with metastatic or aggressive disease (66). Therefore, the value of quantifying nerve infiltration by pathologic examination of clinical specimens to predict patient outcome or treatment response should now be investigated in large retrospective and prospective cohorts of patients with cancer.…”
Section: Diagnostic and Prognostic Value Of Nerves And Neurotrophic Fmentioning
confidence: 99%
“…Isoproterenol of sympathetic nerve activation factor has no direct effect on migration and invasion of prostate cancer cells Psychological distress was highest in men with biochemical recurrence and elevated clinical symptoms [21]. As chronic stress has been linked to cancer progression [7][8][9], whether increasing stress hormone in sympathetic outflow, typically caused by chronic stress, could directly alter migration and invasion of prostate cancer cells is of particular interest. Therefore, we first determined whether 10 μM isoproterenol(ISO), a non-selective bAR agonist as a pharmacological surrogate of sympathetic nerve activation [8], increased migration and invasion of human prostate cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence showed that persistent secretion of stress-related hormones and neurotransmitters plays pivotal roles in the initiation and promotion of tumors [7]. Isoproterenol (ISO), a non-selective b-adrenergic receptor (bAR) agonist as a pharmacological surrogate of sympathetic nerve activation, promoted invasion and metastasis of tumors both in vitro and in vivo [8][9][10]. Current studies demonstrated that central and sympathetic nervous systems activated by chronic stress contributed to the tumor metastasis through b2-adrenergic receptor (b2AR) [11].…”
Section: Thatmentioning
confidence: 99%
“…Yapılan yeni çalışmalar göstermiştir ki kronik stres ve artmış beta-adrenerjik sinyaller akciğerlerde bir "metastatik" niş oluşturmakta, böylece akciğer kanser hücrelerinin kolonizasyonuna yol açmaktadır. Bu niş oluşumu propranolol tarafından inhibe edilmiştir 23 . Nagaraja ve meslektaşları diğer yakın zamanlı çalışmalarında beta adrenerjik reseptör sinyali ile tümör stroması arasındaki ilişkiyi araştırmıştır 24 .…”
Section: Hücrelerin Ikilenme Zamanının Belirlenmesiunclassified